2012
DOI: 10.1177/1094670511430530
|View full text |Cite
|
Sign up to set email alerts
|

Dibs! Customer Territorial Behaviors

Abstract: Third Place'' servicescapes are often created to reflect home-like characteristics, expecting customers to relax, mingle, and consume their purchases. Yet, customers coopt the space, often using it as an extension of workplaces or homes. In pursuit of undistracted privacy, customers engage in territorial behaviors that communicate to other customers that intrusion is not welcome. While place attachment by loyal customers is positive for service providers, territorial behavior can have negative implications for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 62 publications
(76 reference statements)
7
50
0
5
Order By: Relevance
“…This study made use of a laboratory-like setting with a single treatment, where a single group of test units was exposed to the treatment, and then the measurements were taken (Malhotra, 2007). The usage of photographs of environments is gaining popularity in servicescape studies (e.g., Booms and Bitner, 1982;Godey et al, 2009;Griffiths and Gilly, 2012), and studies have shown that color photographs will accurately reflect on-site responses (Stamps, 2004), thereby attesting to the ecological validity of this approach. Thus, photographs were used as the treatment.…”
Section: Methodical Approachmentioning
confidence: 99%
“…This study made use of a laboratory-like setting with a single treatment, where a single group of test units was exposed to the treatment, and then the measurements were taken (Malhotra, 2007). The usage of photographs of environments is gaining popularity in servicescape studies (e.g., Booms and Bitner, 1982;Godey et al, 2009;Griffiths and Gilly, 2012), and studies have shown that color photographs will accurately reflect on-site responses (Stamps, 2004), thereby attesting to the ecological validity of this approach. Thus, photographs were used as the treatment.…”
Section: Methodical Approachmentioning
confidence: 99%
“…A consumer with strong attachment to and psychological ownership for Mercedes cars, for instance, might be reluctant to book a car from a car-sharing platform if only Fords are available. Consumers who feel psychological ownership for a “third place”––a social space other than at home or work, such as a seat in a café, bar, or park––may be more likely to visit it but will linger in that space (Griffiths and McGilly 2012). Firms may wish to keep psychological ownership low for access-based and experiential goods so that consumers are more receptive to a variety of goods and brands, or turn over quickly.…”
Section: Trend 3: Expansion Of Personal Datamentioning
confidence: 99%
“…Findings from studies investigating dysfunctional behaviors by service customers (e.g., Harris and Reynolds 2004; Reynolds and Harris 2009) suggest potential negative consequences of customer copresence. Likewise, physical proximity among customers can adversely influence their perceptions (Grewal et al 2003; Xu, Shen, and Wyer 2011; Zhou and Soman 2003) and lead to territorial behaviors (Griffiths and Gilly 2012).…”
Section: Literature On Customer Copresence: a Fragmented Picturementioning
confidence: 99%